Modelagem dos níveis freáticos do sistema aquífero Bauru (SAB) em diferentes usos da terra no município de Assis - SP - Nava, Aira [UNESP] (2015)
Groundwater outstands for good quality, low withdrawing cost and relative abundance in the State of São Paulo. In the Médio Paranapanema river basin, the Bauru Aquifer System (BMS) is a strategic reserve, its water monitoring is essential for a sustainable way of exploration, and the aquifer keeps developing its role in supplying water for the region. All of the state territory aquifers are exposed to progressive deterioration, given the impacts to geological structures by growing urban settlement, industrial and agricultural blast climbing.Pressure inputted by agricultural and forestry systems in groundwater recharge areas is an important decision variable to water resources planning in the basin. The identification of aquifer responses to the use of land can be done using groundwater monitoring data and time series models. In this context, it have been highlighted the importance of studying the behavior and use of water in the basin, to determine the evaluation of water resources in time and space and measure the impact of modification on the basin hydrological processes. Based on these premises, this study aimed to verify the effects of different crops in the oscillation processes of groundwater levels in the study area. And the application of models based on observations and time series of groundwater levels to understand the processes occurring during the hydrologic cycle and affect the availability of groundwater resources of the Bauru Aquifer System in Assis / SP. Results have shown a distinct behavior between the wells located in the same geological formation, but with different land uses. It have noted that agriculture levels were more sensitive to seasonal variations and the management practices employed there, denoting local flow cells, while in wooded conservation area, where there is no human disturbance, monitoring data reflect the flow base toward the nearest drain, mainly influenced ...